The human pain system exhibits higher-order plasticity (metaplasticity) - Magerl, Walter; Hansen, Niels; Treede, Rolf-Detlef; Klein, Thomas (Neurobiology of learning and memory, 2018)
The human pain system can be bidirectionally modulated by high-frequency (HFS; 100Hz) and low-frequency (LFS; 1Hz) electrical stimulation of nociceptors leading to long-term potentiation or depression of pain perception (pain-LTP or pain-LTD). Here we show that priming a test site by very low-frequency stimulation (VLFS; 0.05Hz) prevented pain-LTP probably by elevating the threshold (set point) for pain-LTP induction. Conversely, prior HFS-induced pain-LTP was substantially reversed by subsequent VLFS, suggesting that preceding HFS had primed the human nociceptive system for pain-LTD induction by VLFS. In contrast, the pain elicited by the pain-LTP-precipitating conditioning HFS stimulation remained unaffected. In aggregate these experiments demonstrate that the human pain system expresses two forms of higher-order plasticity (metaplasticity) acting in either direction along the pain-LTD to pain-LTP continuum with similar shifts in thresholds for LTD and LTP as in synaptic plasticity, indicating intriguing new mechanisms for the prevention of pain memory and the erasure of hyperalgesia related to an already established pain memory trace. There were no apparent gender differences in either pain-LTP or metaplasticity of pain-LTP. However, individual subjects appeared to present with an individual balance of pain-LTD to pain-LTP (a pain plasticity “fingerprint”).